African swine fever incursion risks in Latin America and the Caribbean: informal and legal import pathways - Arcega Castillo, Guillermo; Schultze, Michelle L.; Schulte, Rachael; Schambow, Rachel A.; Hervé-Claude, Luis Pablo; León, Emilio A.; Perez, Andres M. (Frontiers in Veterinary Science, 2025)
African swine fever (ASF) is a devastating hemorrhagic disease of swine with high mortality rates and severe socioeconomic impacts on affected pig industries. In 2021, ASF was reported in the Americas for the first time in 40 years, prompting risk assessments for its introduction and spread. This study evaluates ASF incursion risk across 40 territories in the Caribbean, Central America, North America, and northern South America. A structured, multi-step assessment synthesized peer-reviewed literature, government reports, gray literature, and epidemiological databases to classify two primary ASF incursion pathways: informal imports (e.g., traveler-carried pork, illegal migration, unregulated waste disposal) and legal imports (e.g., trade in live swine and pork products). Territories were categorized as “Probable,” “Unlikely,” or “Unknown,” with certainty levels (Low, Medium, High) based on data robustness. Results indicate ASF incursion is “Probable” (Medium certainty) via informal or formal imports in the Bahamas, British Virgin Islands, Colombia, Cuba, Jamaica, Mexico, Panama, Puerto Rico, Venezuela, Turks and Caicos, and the U.S. Virgin Islands. In contrast, Barbados, Bermuda, Costa Rica, El Salvador, and Guyana were classified as “Unlikely” (Medium certainty) to experience an ASF outbreak under current conditions. Due to insufficient data, 24 territories were categorized as “Unknown” (Low certainty), highlighting critical knowledge gaps. These findings emphasize the need for enhanced surveillance, systematic data-sharing, and regional collaboration to improve risk assessments and implement effective ASF prevention measures in the Americas.